Estratégias de planejamento frente à rigidez do plano plurianual: análise de casos setoriais no Estado de Minas Gerais - Pinheiro Júnior, Fernando Antônio França Sette (2018)
We analyze the planning strategies against the rigidity of the Pluriannual Plan, by analyzing the relationship between the complementary practices of government planning in relation to the plasters from the PPA, in order to verify how these practices are able to overcome the engagements coming from the PPA. From a methodological point of view, the thesis is a comparative case study of two Minas Gerais state secretariats, the State Secretariat of Education (SEE) and the State Secretariat for Development and Integration of the North and Northeast (SEDINOR) in the period from 2011 to 2014. The work showed from the trajectory of the practices of governmental planning, that it ceased to be seen as a merely technical instrument, and began to be seen as an instrument of political action. The trajectory showed two conceptions of governmental planning: one of strictly technocratic character and the other of a technicalpolitical nature, which can be analyzed by the methodology of Situational Strategic Planning. When analyzing the current Brazilian government planning solidifies under the structuring of the PPA, of a technocratic character, not fitting the conception of governmental planning as an instrument of political action, making necessary the adoption of complementary practices of governmental planning that fit to this conception. From the interviews it was found that these complementary practices are able to adapt to the political-institutional context, since they cover the facts about which politicians do not present governability and / or the real State capacity of State action. In addition, these complementary practices are not legal or bureaucratic, which allows changes. However, it is worth mentioning that the PPA has the fundamental role of defining the actions of government and of agreeing a compromise between representatives and represented, and complementary practices should only make the necessary adjustments.